2014
DOI: 10.1155/2014/346405
|View full text |Cite
|
Sign up to set email alerts
|

Seed Dispersal and Germination Traits of 70 Plant Species Inhabiting the Gurbantunggut Desert in Northwest China

Abstract: Seed dispersal and germination were examined for 70 species from the cold Gurbantunggut Desert in northwest China. Mean and range (3 orders of magnitude) of seed mass were smaller and narrower than those in other floras (5–8 orders of magnitude), which implies that selection favors relatively smaller seeds in this desert. We identified five dispersal syndromes (anemochory, zoochory, autochory, barochory, and ombrohydrochory), and anemochorous species were most abundant. Seed mass (F = 3.50, P = 0.01), seed siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 56 publications
(78 reference statements)
2
12
1
4
Order By: Relevance
“…Several authors highlighted the direct relationship between germination response and environmental factors (Liu et al, 2014;Miranda et al, 2009;Pugnaire et al, 2006). Similarly, this study demonstrated the close relationship between annual rainfall amount and seasonal distribution and the adaptive strategies in seed ecophysiology of plants under water stress in saline soils.…”
Section: Discussionsupporting
confidence: 75%
“…Several authors highlighted the direct relationship between germination response and environmental factors (Liu et al, 2014;Miranda et al, 2009;Pugnaire et al, 2006). Similarly, this study demonstrated the close relationship between annual rainfall amount and seasonal distribution and the adaptive strategies in seed ecophysiology of plants under water stress in saline soils.…”
Section: Discussionsupporting
confidence: 75%
“…Although variations in seed shape are classically interpreted almost wholly as adaptations for dispersal, some features of shape may be thrust upon a seed by the conditions inside the ovary in which it develops [ 40 ]. Liu et al [ 41 ] examined 70 species from the cold Gurbantunggut Desert in northwest China and identified five dispersal syndromes (anemochory, zoochory, autochory, barochory, and ombrohydrochory). Barochorous species were significantly smaller and rounder than the others but did not find a correlation between seed shape and germination percentage.…”
Section: Seed Shape Regulationmentioning
confidence: 99%
“…The variation in colour and size of seeds and its effects on germination of legumes has been reported by several researchers (Coste et al 2001, Bhatt et al 2016a). In a comprehensive study of the germination of 70 species from the cold Gurbantunggut Desert in northwest China, Liu et al (2014) found that smaller seeds germinated faster than larger ones. Such a germination behaviour and strategy would allow for smaller seeds to colonize suitable microsites in advance of larger-seeded species (Norden et al 2009, Liu et al 2014.…”
Section: Discussionmentioning
confidence: 99%